Strain Versus 2D Shear-Wave Elastography Parameters—Which Score Better in Predicting Thyroid Cancer? - Andreea Borlea; Ioan Sporea; Alexandru Popa; Mihnea Derban; Laura Taban; Dana Stoian (Applied Sciences, 2022)
The aim of this study is to assess the diagnostic performance of strain elastography (SE) versus 2D shear-wave elastography (2D-SWE) by providing a head-to-head comparison of the two methods. Ninety-four thyroid nodules were evaluated using conventional ultrasound (B-mode) and SE, namely, real-time elastography (RTE) with a Hitachi Preirus machine (Hitachi Inc., Tokyo, Japan) and consecutively, 2D-SWE with SuperSonic Mach30 equipment (Supersonic Imagine, Aix-en-Provence, France). The results were compared in all cases to the pathology reports. Out of the 94 nodules, 29 (30.9%) were malignant. Both SE and 2D-SWE parameters proved to have excellent diagnostic quality, with comparable results. The mean elasticity index was the best parameter for the 2D-SWE (AUC 0.912); for a cut-off value of 30.5 kPa, it predicts thyroid malignancy with a sensitivity of 79.3%, specificity of 95.38%, NPV of 91.2% and PPV of 88.5%. The best parameter for SE was the strain ratio (cutoff > 3.9; sensitivity 82.7%; specificity 92.3%; AUC 0.905). When integrated in the ultrasound risk algorithm, both elastography methods improved the diagnostic performance: AUC 0.764 vs. 0.886 vs. 0.861 for B-modes: B-mode + 2D-SWE vs. B-mode + SE. We concluded that elastography adds diagnostic value in predicting malignancy, both when Hitachi RTE and SuperSonic 2D-SWE were used.